Neurogenic bladder function disorders in patients with meningomyelocele: S2k guidelines on diagnostics and therapy - Stein, R.; Assion, C.; Beetz, R.; Buerst, M.; Cremer, R.; Ermert, A.; Goepel, M.; Kuwertz-Broeking, E.; Ludwikowski, B.; Michael, T.; Pannek, J.; Peters, H.; et al. (Urologe, 2015)
The treatment of children and adolescents with meningomyelocele has experienced a clear change in the last 30 years. The establishment of pharmacotherapy, clean intermittent catheterization (CIC) and infection prophylaxis have improved the prognosis for patients and have led to new therapeutic strategies. The interdisciplinary cooperation between neonatologists, neurosurgeons, pediatric neurologists, pediatric urologists, pediatric nephrologists, pediatric orthopedists and pediatric surgeons leads to optimization of individualized therapy. These guidelines present definitions and classifications, investigations and timing which are described in detail. The conservative and operative therapy options for neurogenic bladder function disorders are described and discussed with reference to the current literature. The brief overview provides in each case assistance for the treating physician in the care of this patient group and facilitates the interdisciplinary cooperatio
EVALuna2:18927